Peningkatan Hasil Belajar Akuntansi Keuangan Melalui Model Cooperative Learning Tipe Jigsaw - Warneri Warneri (Jurnal Teknologi Pendidikan, 2017)
This research aimed is toimproving the students’ learning achievement and activities through improving accounting learning process by implementing jigsaw type cooperative learning model.Using action research method, this research was done through planning, implementation, observation and reflection. This action research was conducted in two cycles. Every cycle was done in eight metings.The data of learning achievement were collected through materials comprehension test before the action, after the first cycle action, after the second cycle action, and after all actions had been completed. The data of the students’ activities were collected through observations during the teaching and learning processes were administered. The research resulted in the improvement of learning achievement and activities in the process of learning accounting through the implementation of jigsaw type cooperative learning model. Keywords: Learning Achievement,Financial Accounting,Cooperative Learning, Jigsaw Type